Review paperThe theoretical basis for application of NB-UVB radiation in dermatology - Obtułowicz, Aleksander; Antoszczyk, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
In recent years great interest in phototherapy as an effective method for treatment of skin diseases has been observed. The biological effect of UV depends on the dose and the wavelength as well as patients’ sensitivity to UV. Recently particular interest is more focused on narrow-band UVB (311-313 nm), which is considered safe and effective treatment for a variety of skin diseases. In the article the immunomodulatory and immunosuppressive mechanism of UVB 311 nm is described. The benefits and complications typical for this method are presented.